Pengaruh Iklim Komunikasi dan Motivasi terhadap Kinerja Dosen pada Akademi Maritim Indonesia (AMI) Medan: Penelitian - Muhammad Sahid (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Based on the background described above, the problem is formulated as follows: 1. How much influence the climate of communication on improving the performance of lecturers at the Indonesian Maritime Academic Medan. 2. How big is the influence of motivation on the performance of lecturers in the Indonesian Maritime Academic Medan. 3. How much influence the climate of communication and motivation on improving the performance of lecturers at the Indonesian Maritime Academic Medan. Communication Climate regression coefficient of 0.420 shows that the communication climate variable has a positive influence on lecturer performance by 42%, meaning that the better the communication climate which consists of Responsibility, responsibility, Warmth, Support, Conflict will affect the performance of lecturers at the Indonesian Maritime Academy in Medan. Motivational regression coefficient of 0.496 indicates that motivation has a positive influence on lecturer performance by 49.6%, meaning that the higher the level of motivation consisting of physiological, security, appreciation, group needs, self-actualization will lead to an increase in lecturer performance. The magnitude of the coefficient of determination or R2 = 0.807, can be interpreted that 80.7% of the dependent variable is the lecturer performance variable in the model can be explained by the independent variable that is the climate communication variable and lecturer motivation, while the remaining 13% is influenced by other variables not tested in the study this.